The Impact of Social, Economic and Cultural Factors on Food Consumption Patterns in Oemasi Village, Kupang District - Philipus Imanuel A E Mangngi Uly; S.P Manongga; Sarcy M Toy (Universitas Nusa Cendana, 2022)
The consumption pattern is one of the direct factors of nutritional status. The amount, type, and frequency of daily food consumption could affect intelligence, body resistance to diseases, and work productivity. This study analyzed the influence of socio-economic and cultural factors on food consumption patterns. This study used a cross-sectional design with 139 homemakers selected using the simple random sampling technique. The research was conducted in Oemasi Village, Nekamese Sub-District, Kupang District, from March to April 2020. The statistical test used was a multiple logistic regression test with alpha= 0.05. The research found that mother's education (p-value = 0.025) and family income (p-value = 0.003) affected food consumption patterns (p-value = 0.025, 0.003, consecutively), while mother's occupation, the number of household members, dietary restrictions, staple food preferences, and feeding priority had no effect on food consumption patterns (p-value =0.70, 0.63, 0.34, 1.08, and 0.85, respectively). Health workers should regularly educate local people about the importance of good and healthy food consumption patterns.